Upaya Guru Pendidikan Agama Islam Dalam Mengatasi Tantangan Pembelajaran Bagi Generasi Alpha - Muhadditsir Rifai; Ery Khaeriyah (Sekolah Tinggi Ilmu Tarbiyah Buntet Pesantren Cirebon, 2026)
This study aims to determine the implementation of Islamic Religious Education (PAI) learning, identify the challenges faced by PAI teachers, and determine the efforts made by teachers in overcoming these challenges in the Alpha generation at SMP Negeri 2 Plered, Cirebon Regency. This study uses a descriptive qualitative approach, data collection techniques through observation, interviews and documentation. Data analysis techniques use data reduction, data presentation, drawing conclusions and verification. The results of the study show that: 1) The implementation of PAI learning is carried out through three stages: introduction (reading prayers, attendance, and reviewing materials to build learning readiness), core (delivery of materials with varied methods and visual media to maintain student focus), and closing (conclusion, providing reinforcement by asking questions to support reflection and learning independence and reading prayers). 2) Challenges faced by PAI teachers include: the behavior of Alpha generation students who are less focused, tend to be noisy, and limited facilities such as the lack of projectors and the absence of LKS. 3) Teachers' efforts to overcome these challenges by providing simple learning media (LKPD, pictures, cardboard), the use of varied methods, a personal approach to students, and remedial programs for those who have not reached the KKM